An easy-to-use capsicum delivery system for crop-raiding elephants in Zimbabwe: preliminary results of a field test in Hwange National Park - Le Bel, Sébastien; Taylor, Russell; Lagrange, Mike; Ndoro, Onias; Barra, Marc; Madzikanda, Hillary (Pachyderm, 2010)
With the increase of elephant populations in southern Africa and the expansion of human settlements into wildlife areas, local communities are faced with increasingly numerous cases of human-elephant conflict (HEC), which require a combination of mitigation approaches for there management. Although chilli has been tested with success on crop-raiding elephants, its utilization on a larger scale has been limited by the difficulty of finding a low-cost, easy-to-use capsicum delivery system. Two types of dispensers were developed: a catapult using clay balls and a gas-dispenser using ping-pong balls. The two prototypes were tested on a firing range and the gas-dispenser on elephants in Hwange National Park. The mean shooting distance was 46 m. Fifty-four percent of shots released chilli oil extract on the targeted animal. Following shooting, 46% of elephants ran away, 29% backed up walking and 25% did not change their behaviour. Significant variation in agonistic behaviour was due to the success of chilli oil extract spreading onto the elephant. Improvements in the ballistic performance of the gas-dispenser have been undertaken and trials in its application with communities are in progress. Further research is planned to separate the individual effect of projectile impacts, bang and chilli itself and to assess the longer-term deterrence properties of capsicum on elephants. Avec l’augmentation des populations d’éléphants en Afrique australe et l’expansion des peuplements humains jusque dans les aires de la faune, les communautés locales font face à des cas de plus en plus nombreux de conflits homme-éléphant (CHE) qui exigent une combinaison d’approches d’atténuation pour les gérer. Même si le piment a été testé avec succès à l’encontre des éléphants maraudeurs, son utilisation à une grande échelle a été limitée par la difficulté de trouver un système de livraison de piment peu coûteux et facile à utiliser. Deux types de distributeurs ont été développés: une catapulte qui utilise des balles en argile et un distributeur de gaz qui utilise une balle de ping-pong. Les deux prototypes ont été testés sur un champ de tir et le distributeur de gaz sur les éléphants dans le Parc national de Hwange. La distance moyenne de tir était de 46 m. Cinquante-quatre pour cent de coups ont dégagé un extrait d’huile de piment sur l’animal visé. Suite au tir, 46% des éléphants se sont enfuis, 29% ont fait marche arrière et 25% n’ont pas changé leur comportement. Une variation importante dans le comportement agonistique était due au succès de l’extrait d’huile de piment qui se répandait sur l’éléphant. Les améliorations dans la performance balistique du distributeur de gaz ont été entreprises et les essais dans son application avec les communautés sont en cours. Une recherche supplémentaire est prévue pour séparer l’effet individuel des impacts des projectiles, du coup et du piment lui-même et pour analyser les propriétés de dissuasion du piment à plus long terme sur les éléphants.